2013
DOI: 10.1111/ajps.12054
|View full text |Cite
|
Sign up to set email alerts
|

Informing the Electorate? How Party Cues and Policy Information Affect Public Opinion about Initiatives

Abstract: Citizens in representative democracies receive party endorsements and policy information when choosing candidates or making policy decisions via the initiative process. What effects do these sources of information have on public opinion? We address this important question by conducting survey experiments where citizens express opinions about initiatives in a real-world electoral context. We manipulate whether they receive party cues, policy information, both, or neither type of information. We find that citize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
154
1
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 248 publications
(162 citation statements)
references
References 32 publications
6
154
1
1
Order By: Relevance
“…That partisanship exerts a powerful influence on preference formation is well documented (Bartels 2002;Cambell et al 1960;Goren 2002;Jerit and Barabas 2012), and with few exceptions (Boudreau and MacKenzie 2014;Bullock 2011), research suggests that the citizenry follow elite party endorsements even at the expense of relevant information (Cohen 2003;Lau and Redlawsk 2001;Rahn 1993). This paper shows that the influence of partisanship in opinion formation is not unbounded.…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…That partisanship exerts a powerful influence on preference formation is well documented (Bartels 2002;Cambell et al 1960;Goren 2002;Jerit and Barabas 2012), and with few exceptions (Boudreau and MacKenzie 2014;Bullock 2011), research suggests that the citizenry follow elite party endorsements even at the expense of relevant information (Cohen 2003;Lau and Redlawsk 2001;Rahn 1993). This paper shows that the influence of partisanship in opinion formation is not unbounded.…”
Section: Discussionmentioning
confidence: 55%
“…This is a notable gap given that it strikes at the heart of opinion formation-to what extent do people rely on partisanship and issue attitudes in decision-making? The answer has important implications for our understanding of elite influence, the scope and source of distortions in preference formation, and is central to contemporary debates about the relative influence of partisanship and issue information in decision-making (Boudreau and MacKenzie 2014;Bullock 2011).…”
mentioning
confidence: 99%
“…Recent studies in the U.S. show that a voter's partisan biases affect their willingness to internalize new information (e.g. Jerit and Barabas 2012; Boudreau and MacKenzie 2014;Bullock 2011;Gerber and Huber 2010), while European studies have indicated that poorly informed voters are most sensitive to new information (e.g. Duch 2001).…”
Section: Voter Sophisticationmentioning
confidence: 99%
“…Do you prefer Mar over Lee or Lee over Mar?'' Previous research testifies to the importance of signals from political parties in shaping voters' choices (Popkin 1991;Sniderman and Bullock 2004;Boudreau and MacKenzie 2014). There is also considerable evidence that they facilitate spatial voting in national politics (Sniderman and Stiglitz 2012).…”
Section: Methodsmentioning
confidence: 99%